2021
DOI: 10.1177/00220574211026905
|View full text |Cite
|
Sign up to set email alerts
|

The Importance, Opportunities, and Challenges of Empirically Assessing Character for the Promotion of Flourishing

Abstract: The article discusses the importance of quantitative empirical character assessment for better understanding the formation of character and for promoting virtue and thereby also human flourishing. Attention is given to a number of challenges in developing character survey items along with criteria for evaluating items and examples of successes and failures in item development. Discussion is also given to future opportunities to include character assessments in large longitudinal cohort studies, to develop scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…While this study found little evidence that character strengths, as assessed by the present items, were related with subsequent well-being in other domains of flourishing, several things should be held in mind. First, it may be more difficult to self-report on character strengths than on other domains of flourishing due to social desirability or a lack of self-awareness; alternatively, it may also be the case that the these newly proposed items are not the best item formulations for the purposes of self-assessment 73 . This may have been the case for example with the item "I always know the right thing to do, " which had negative associations with subsequent flourishing.…”
Section: Discussionmentioning
confidence: 99%
“…While this study found little evidence that character strengths, as assessed by the present items, were related with subsequent well-being in other domains of flourishing, several things should be held in mind. First, it may be more difficult to self-report on character strengths than on other domains of flourishing due to social desirability or a lack of self-awareness; alternatively, it may also be the case that the these newly proposed items are not the best item formulations for the purposes of self-assessment 73 . This may have been the case for example with the item "I always know the right thing to do, " which had negative associations with subsequent flourishing.…”
Section: Discussionmentioning
confidence: 99%
“…As the analysis of this past year reveals, this data infrastructure should attend to measures of implementation readiness and measures of character education implementation and outcomes. While validated measures of character virtues exist (see, for example VanderWeele, 2021 in this issue), the majority of KPCEL members were focused on proximal aims such as building will and capacity for embedding character education approaches, developing resources aligned to existing program aims, and testing out the implementation feasibility of new protocols and practices. Having a centralized data infrastructure can help facilitate data use, as teams do not have to devote limited time and resources to doing that work independently (Russell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although historical measures of flourishing tended to focus exclusively on psychological well-being (e.g., happiness or life satisfaction), the development of more sophisticated conceptional frameworks include domains of physical health, virtue strengths [34,35], meaning and purpose, and financial and material resources that are undeniably linked to sustained flourishing over time (see Box 2) [36]. In Western nations, those who score high on wellbeing scales perceive their family background as wealthy, rate their general health status as excellent, and report higher perceived social resource [37]; for example, optimism, a psychological asset oft-associated with flourishing and healthy lifestyle habits [38], does not sit on an equitable playing field-it is highly associated with socioeconomic advantage [39][40][41][42].…”
Section: Flourishing-people Places and Planetmentioning
confidence: 99%